False aneurysm of common iliac artery post lumbar disc surgery. - Vallverdú, Martín; Sánchez, Luis; Sánchez, Luis; Sanguinetti, Julio; Delgado, Alicia; Crestanello, Francisco (Cirugía del Uruguay, 1987)
A case of false aneurysm of the rlght common lliac artery alter lumbar disc surgery treated by exclusion and aorto-iliac by pass are reported. A, review of the literature is done with considerations about the frequency, pathogenesis and diagnosis of this vascular injury.